Desigualdades sociales en salud y la pandemia del COVID‑19: el caso de España - Marta Aguilar Gil; José María Bleda García (e-cadernos ces)
The main objective of this research is to identify the social inequalities in health among Spaniards as a consequence of the COVID‑19 pandemic. The documentary observation technique has been chosen to analyse selected technical and scientific documents published in the years of the pandemic. Of the results obtained, the following stand out: The fundamental role played by the State and the family to confront the pandemic; the visibility of the weaknesses in the National Health System that hindered universal access of citizens to health services, especially the most vulnerable groups; the increase in gender-related social inequalities in health, with women having to endure more pressure at home; and, the loss in economic income in the most vulnerable families.